What if it happens in my classroom? : developing skills for expert behaviour management - Sida-Nicholls, Kate. (Milton Park, Abingdon, Oxon : Routledge, 2012)
'Why can't I stop my students from being noisy as they leave my classroom? What can I do when a student is texting on their phone in my lesson? How can I stop a student from constantly tapping their pen while I am talking? Sound familiar? Chewing gum, dropping litter, swearing, late homework and disruptive behaviour in class are just a few of the issues that teachers have to face every day in the classroom. How you choose to respond to these incidents, however minor they may first seem, can have a dramatic impact on the overall quality of your lessons. There is no one answer to behaviour and classroom management as different approaches have to be taken depending on the lesson, the groups of students and even the time of day. This highly practical book guides you through the choices that you need to make when confronted with the sorts of issues that you might face in your classroom. Dealing with the nitty gritty reality of behaviour management, it covers the common problems teachers encounter on a day to day basis and provides a series of realistic and practical solutions and their likely outcomes. Placing you at the centre of the decision making process, it allows you to experiment with a range of options in a reflective and engaging manner to see which of your choices may work and why others may not. This scenario based approach not only lets you explore the various options available to you, but also enables you to see the consequence of your actions. Written by an experienced teacher, this fun and interactive book is essential reading for all trainee and qualified teachers who want a fresh approach to behaviour management in their classrooms'--
Includes index.
Keywords: Classroom management; Behavior modification; Problem children -- Behavior modification; School discipline